Investigating the Reliability of the Knee Joint Flexors and Extensors Muscles Length Tests Modified to Meet the Requirements of Scientific Research - Rafał Gnat; Anna Gogola; Agnieszka Polaczek; Piotr Woźniak; Tomasz Wolny (Journal of Rehabilitation)
Objective This study evaluates the intra- and inter-rater reliability of modified versions of the widely used clinical tests for assessing knee flexor and knee extensor muscle length. These tests are fundamental components of postural assessments in children and adolescents, helping to identify postural abnormalities and inform appropriate treatment or preventative strategies. The findings can determine the feasibility of using these modified versions in scientific research. Materials & Methods A total of 76 children (37 girls) with a mean age of 13.24 years were included. The two evaluators took the measurements on the same day, as well as with breaks lasting two and five days. The following indices of reliability were calculated: Intraclass correlation coefficients (ICC), standard errors of measurement, and smallest detectable differences. Results The outcomes of both muscle length tests demonstrated good to excellent reliability, regardless of whether the measurements were conducted by the same evaluator after 2 or 5 days, or by different evaluators on the same day and after similar intervals. The lowest calculated ICC of 0.79 was for the knee flexors length test on the left side of the body. In all remaining cases, ICCs>0.80 were obtained. Conclusion After specific modifications, there is a possibility of obtaining a high level of reliability of the two addressed muscle length tests, which justifies the utilization of the modified versions in scientific settings.